Programmed death-ligand 1 expression in gastric cancer by the combined positive score using the PD-L1 IHC 28–8 pharmDx test: a single institution’s experience - Tomomi Hamaguchi; Kyoko Furusawa; Mamoru Watanabe; Kei Hayashi; Mitsuhiro Furuta; Yasuhiro Inokuchi; Satoshi Kobayashi; Makoto Ueno; Yuta Nakayama; Mie Tanabe; Junya Morita; Kyohei Kanematsu; et al. (Japanese Journal of Clinical Oncology, 2026)
Abstract Background Programmed death-ligand 1 (PD-L1) Combined Positive Score (CPS) is a biomarker of nivolumab efficacy in advanced gastric cancer (AGC). Reported CPS ≥ 5 in AGC has been inconsistent across studies. We aimed to examine the distribution of CPS in real-world clinical practice using the Dako PD-L1 IHC 28–8 pharmDx (Dako 28–8) assay and to evaluate its clinical utility. Methods We retrospectively assessed CPS using Dako 28–8 in 138 patients with AGC treated at our institution between January 2022 and December 2022. Results The numbers of patients with CPS ≥ 5, 1 ≤ CPS < 5, and CPS < 1 were 65 (47.1%), 50 (36.2%), and 23 (16.7%), respectively. Among the patients evaluated for microsatellite instability (MSI) or tumor mutation burden (TMB), MSI-high was identified in 3/32 (9.4%), 2/31 (6.5%), and 1/20 (5.0%), while TMB-high was identified in 5/14 (35.7%), 4/20 (20.0%), and 2/11 (18.2%) in the CPS ≥ 5, 1 ≤ CPS < 5, and CPS < 1 groups, respectively. Nivolumab combination therapy was administered as first-line treatment in 14, 10, and 11 patients in the CPS ≥ 5, 1 ≤ CPS < 5, and CPS < 1 groups, respectively. Median Progression-free survival was 5.6 months in CPS ≥ 5, 5.9 months in 1 ≤ CPS < 5, and 6.5 months in CPS < 1. Conclusion The frequency of CPS ≥5 in patients with AGC was approximately half of the total population. Because TMB-high tumors were identified in some patients with CPS < 5, further studies are needed to clarify the potential role of TMB in predicting ICI responsiveness in this population.